Sulphamic Acid Corrosion Inhibition: A review - Ekere, Isaac; Agboola, Oluranti; Ayeni, Augustine (ASEAN Journal of Chemical Engineering, 2024)
Sulphamic acid solutions are frequently employed in industrial equipment cleaning, descaling, and other processes, such as acidizing low-temperature carbonate reservoirs. Several researchers have reported the inhibition of corrosion of different metals and alloys in sulphamic acid using inhibitors like tryptophan, olive leaf, azo dyes, chitosan, Juniperus, cystine, s-containing amino acids, etc. Sulphamic acid is soluble in water and is classified as a strong inorganic acid in solution. Still, its corrosiveness is significantly lower than other acids, such as sulphuric acid and hydrochloric acid. Sulphamic acid and inorganic acid cleaners based on sulphamic acid are used extensively in diversified cleaning applications. They are superior to other mineral acids due to lower corrosion rates and the absence of corrosive fumes evolution. For this reason, mild and stainless-steel cleaning employs sulphamic acid. Nevertheless, the application of sulphamic acid in industrial cleaning is only partially without its drawbacks, as the cleaning action usually leads to dissolution and loss of base metals. Industrial practice includes adding corrosion inhibitors to minimize equipment corrosion damage. The current review paper summarises recent research on sulphamic acid corrosion inhibition. It summarizes the various corrosion inhibitors employed to mitigate corrosion in various pieces of equipment made of metals or metal alloys exposed to sulphamic acid in different conditions. The researchers employed weight loss, electrochemical methods, and surface characterizations. In literature and practice, the usual concentration of sulphamic acid for cleaning is 5 – 10 wt. % at a temperature range of 55 – 65 ℃. The inhibition efficiencies observed varied from 84 – 97.3 %. The examinations include studies of the effects of temperature, concentration, immersion time, and stirring velocity.